Small Hydro Power Plant in the Kyrgyz Republic : Assessment of Potential and Development Challenges - World Bank (World Bank, Washington, DC, 2017)
The objectives of the analysis presented in this report are to: 1) affirm the existing estimates of small hydropower technical potential and assess the economic viability of small hydropower plant (SHPP) sites in the Kyrgyz Republic, 2) estimate the fiscal or financial support that would be required to foster SHPP development in the short- and longer-term; and 3) analyze the legal and regulatory framework for SHPPs, including challenges and barriers for private investors.